UPAYA MENINGKATKAN KOMPETENSI GURU-GURU BAHASA JERMAN MELALUI PELATIHAN PENELITIAN TINDAKAN KELAS - Haryati, Isti; Santoso, Iman; Sudarmaji; Rikfanto, Aditya; Mulyati, Retna Endah Sri; Megawati, Sri (Transpublika Publisher, 2022)
Improving teacher competence is important in learning German. To improve the quality of learning German, the Devotion Team at the Department of German Language Education FBS-UNY held a Classroom Action Research training for German language teachers who are members of the Indonesian German Teacher Association (IGBJI). This Community Service Activity is realized in the form of a 32-hour training (workshop) which is divided into 3 meeting sessions. First session contains an explanation of the theories and methods of Classroom Action Research. Meanwhile, second session contains mentoring activities to find research ideas, and last Session contains presentations of research proposals from selected participants. This training activity is carried out entirely online using the Zoom application. Classroom Action Research training activities can be carried out properly and get the results as planned. The attendance rate of registered participants is in the good category. Average attendance of 50 people per session (69.4%) of the total 72 registrants. Participation of participants in the discussion is also good. At the end of the activity, 23 Classroom Action Research proposals were produced. Thus, German teachers are able to apply the results of this activity by observing the state of learning German in their respective schools and taking scientific steps to carry out action research.